The Cross-Faith Nyadran Tradition: Navigating Popular Religion for Harmonious Living in Contemporary Indonesia - Prihantoro, Hijrian Angga (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study investigates the interfaith Nyadran tradition practiced by the Getas-Temanggung community, addressing the scholarly question of how local religious and ritual practices sustain their relevance amid the intensifying forces of modernization. The research aims to elucidate the dynamics of Nyadran as a form of folk religion and its function in navigating interfaith harmony. Data were obtained through participant observation to capture ritual practices, interviews with interfaith participants, and analysis of pertinent documents. Employing an analytical framework grounded in the concepts of popular religion and religious harmony, the findings reveal that the interfaith Nyadran tradition integrates formal religious values with local customs, thereby creating an inclusive space for interfaith engagement. This ritual promotes social solidarity, cultivates tolerance, and supports ecological harmony through practices that demonstrate respect for nature. The practical implications underscore the significance of respecting and preserving local traditions as a strategy for enhancing social cohesion within the context of modernity, alongside advocating for an inclusive religious ideology as a counter-narrative to fundamentalist and exclusivist perspectives. The study recommends that governmental bodies and religious organizations endorse similar practices as models for strengthening social cohesion in multicultural, multiethnic, and multireligious societies.